Educational Management Publication Trends In The Scopus Database: An Analysis Of The Evolution Of Research Development - Resky Nuralisa Gunawan; Muhammad Imran Nur; Mar’ah Tusshalihah (Penerbit Hellow Pustaka, 2025)
This analysis aims to see publication trends regarding the use of structural equation modeling in the field of education. By using predetermined keywords, researchers obtained 433 documents that had gone through the PRISMA method and analyzed using the R Program. From the analysis results, it can be concluded that research using the Structural Equation Modeling approach in the field of education shows a positive trend from 1984 to 2024, with an annual growth rate of 11.58%, and the peak publication is expected to occur in 2024 with 80 documents. The country with the highest number of publications is China (Asia), with 54 publications (12.50%) and a total of 1,286 citations (12.27%). Jambi University from Indonesia is ranked first with the highest number of publications, namely 14 publications (3.24%). Sustainability Journal (Switzerland) was ranked first with an h-index of 9, recording 387 citations and 19 publications. Researcher Tsai Chin-Chung from National Taiwan Normal University was ranked first with an h-index of 8. The article with the highest number of citations was (Scherer et al., 2019) with 955 citations. The keyword